The Woman Struggle As Seen In Shonda Rhimes Bridgerton Season 1 - Sagustia, Poppy; Aditiawarman, Mac (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This thesis focuses on the characteristics of the main character, Daphne, and the factors that influence her personality in fulfilling that desire. In analyzing Daphne's personality, this thesis uses Sigmund Freud's theory. The method used in this research is descriptive qualitative. The data in this drama is the script of the dialogue, sentences related to the main character who is searching for love and their struggle in choosing a partner in the era of arranged marriages. The data collection technique in this research is the technique of taking notes based on the struggles of love in choosing a partner in the script of Bridgerton season 1 by Shonda Rhimes. The results of this research indicate that in the script of Bridgerton season 1 by Shonda Rhimes. (1) The struggle in choosing love that Daphne experiences during her first season, which she hopes for. (2) Choosing according to one's desires in assessing the desired partner. (3) Deciding on an issue where betrayal, lies, and disappointment occur, testing oneself